2021
DOI: 10.1021/acs.nanolett.1c02641
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Electron Wind Force in the Elastic Regime

Abstract: With continued scaling toward higher component densities, integrated circuits (ICs) contain ever greater lengths of nanowire that are vulnerable to failure via electromigration. Previously, plastic electromigration driven by the “electron wind” has been observed, but not the elastic response to the wind force itself. Here we describe mapping, via electron energy-loss spectroscopy, the density of a lithographically defined aluminum nanowire with sufficient precision to determine both its temperature and its int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The former can be neglected in most cases as it nullifies itself due to the opposite polarity of positive ions surrounded by negative electrons. The electron wind force, generated by the momentum transfer between the electron and lattice, acts in the direction of current flow [27]. In electromigration literature, such directionality creates a convective diffusion mode of atomic mass transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former can be neglected in most cases as it nullifies itself due to the opposite polarity of positive ions surrounded by negative electrons. The electron wind force, generated by the momentum transfer between the electron and lattice, acts in the direction of current flow [27]. In electromigration literature, such directionality creates a convective diffusion mode of atomic mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In electromigration literature, such directionality creates a convective diffusion mode of atomic mass transfer. The high current density also generates Joule heating, which facilitates void growth and creates a positive feedback loop to accelerate the thermal force [26][27][28]. Xu et al [21] reported that the high-density current could increase the material temperature to 600 °C, and the associated thermal force can essentially overcome the activation energy for the grain-boundary diffusion, resulting in grain growth.…”
Section: Introductionmentioning
confidence: 99%
“…However, the occurrence of electromigration needs dozens of hours and the resultant back-stress needs enough time to build up (for the accumulation of vacancy gradient) 40 ; while, with the nanosecond pulse in our experiments, the contribution of electromigration and resultant back-stress should be negligible. It is also noticed that the transient second density-changing effect created by the electron wind can induce a pressure gradient that increases linearly with the distance along the axial direction of sample 43 . But in our experiments, the non-directional migration of ITB mainly proceeded along the radial direction of our samples, and thus the pressure resulted from the electron wind force should be constant or have very limit variation during the ITB migration, which should not influence the conclusion of our experiments.…”
Section: Discussionmentioning
confidence: 95%
“…In an electric field, the conductor is affected by the direct electrostatic force (F e ) generated in the same direction as the electric field, and the electron wind or ion wind force (F w ), generated in the opposite direction as the electric field under the influence of momentum exchange with other charge carriers. [116,117] Therefore, the total driving force F tot that the activated ion inside the electric field receives is…”
Section: Electromigrationmentioning
confidence: 99%
“…In an electric field, the conductor is affected by the direct electrostatic force ( F e ) generated in the same direction as the electric field, and the electron wind or ion wind force ( F w ), generated in the opposite direction as the electric field under the influence of momentum exchange with other charge carriers. [ 116,117 ] Therefore, the total driving force F tot that the activated ion inside the electric field receives is Ftotbadbreak=Fe0.33emgoodbreak+0.33emFwgoodbreak=0.33emq·()ZnormaleZnormalw·E0.33emgoodbreak=0.33emq·Z*·E0.33emgoodbreak=0.33emq·Z*·ρ·J$$\begin{equation} {\stackrel{\to}{F}}_{\mathrm{tot}}={\stackrel{\rightarrow}{F}}_{\mathrm{e}}\ +\ {\stackrel{\rightarrow}{F}}_{\mathrm{w}}=\ q\cdot \left({Z}_{\mathrm{e}}-{Z}_{\mathrm{w}}\right)\cdot \stackrel{\rightarrow}{E} \ =\ q \cdot {Z}^{\ast}\cdot {\stackrel{\rightarrow}{E}}\ =\ q\cdot {Z}^{\ast}\cdot \rho \cdot {\stackrel{\rightarrow}{J}} \end{equation}$$where q is the electric charge of the ions, Z e and Z w are the valences corresponding to the electrostatic and wind forces, respectively, Z* is the effective valence of the material, J is the current density of the conductor, and ρ is the resistivity of the material. Each material for a specific technology node requires a discrete calibration to manage any effects during manufacturing and operation.…”
Section: Interconnect Materials and Critical Issuesmentioning
confidence: 99%